International Comparisons of Government Expenditure Revisited : The Developing Countries 1975-86: Occa Paper No.69. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This chapter discusses the changes that have taken place in the underlying structural relationships determining government expenditures between 1975 and 1986. The paper describes the methodological problems in analyzing the determinants of government expenditure patterns, and the issues involved in making cross-country expenditure comparisons, and the problems confronting country economists in assessing a country's expenditure profile. The Tait-Heller study concluded that the international expenditure comparison (IEC) framework provided a 'starting point' for analysis. In many respects, this conclusion would still appear valid; if anything, the issues associated with using the IEC indices have become more rather than less complex. Data limitations also pose a limiting factor on the usefulness of an analysis of the IEC indices of a country, and even more strongly suggest its use only as complementary to more detailed sectoral and economic analyses of expenditure profiles. The results for the developing countries in the European region are almost identical to those observed in Africa, with the key exception being an increased priority for expenditure on social security and welfare and a decline in the priority attached to education.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet